A COHORT STUDY ON THE EVALUATION OF THE BRAIN BY MAGNETIC RESONANCE IMAGING IN PAEDIATRIC PATIENTS WITH DEVELOPMENTAL DELAY - Jha, Nivedita; Kumar, Deepak; Gupta, Anand Kumar; Kumar, Amit; Suman, Sanjay Kumar (Student's Journal of Health Research Africa, 2024)
Introduction One major neuromorbidity that affects children and may have long-term effects on quality of life is developmental delay (DD). Magnetic resonance imaging (MRI) has become a key tool in evaluating these patients. This study aimed to assess DD in pediatric patients by utilizing magnetic resonance imaging (MRI) to identify underlying brain abnormalities that may contribute to the condition. Methods This hospital-based prospective observational study included 100 pediatric patients referred for MRI brain evaluation due to developmental delay between January 2021 and July 2022. MRI scans were performed using 1.5 Tesla superconducting MRI machines (GE Optima MR360, Optima MR450W GEM, and SIGNA Artist) with appropriate sequences and planes, using sedation, when necessary, under anesthetist guidance. The brain's anatomical structures were assessed systematically for normalcy and maldevelopment, and the findings were categorized into different etiological groups. Results Normal MRI findings were observed in 13% of participants, while 87% showed abnormal results. The most commonly affected anatomical areas were the white matter (52.87%) and the ventricles (44.83%). Of the abnormal cases, 53% were attributed to neurovascular etiologies, such as hypoxic-ischemic encephalopathy (HIE), followed by 14% for congenital and developmental etiology, 13% for metabolic and neurodegenerative disorders, 4% for nonspecific findings, 2% for neoplastic lesions, and 1% for multifactorial causes. Conclusion: Clinical examination and analysis are the first steps in diagnosing developmental delay, but brain imaging should be done to rule out any causes and provide appropriate management. Due to its great soft tissue resolution, the MRI brain is the best imaging modality. Recommendations MRI should be standard in assessing pediatric developmental delay due to its high sensitivity and specificity in detecting abnormalities. It aids in early diagnosis and guides targeted treatment. Larger studies are needed to refine diagnostic criteria and better understand MRI's role.